2007
DOI: 10.1254/jphs.fp0060928
|View full text |Cite
|
Sign up to set email alerts
|

Differences of Cell Growth and Cell Cycle Regulators Induced by Basic Fibroblast Growth Factor Between Nifedipine Responders and Non-responders

Abstract: Abstract. Differences of cell proliferation, cell cycle, and G 1 / S transition regulatory proteins of gingival fibroblasts derived from nifedipine-reactive patient (NIFr) and nifedipine-nonreactive patient (NIFn) in the presence of basic fibroblast growth factor (bFGF) were investigated to elucidate the mechanism of gingival overgrowth associated with nifedipine, one of the Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 29 publications
(41 reference statements)
1
24
0
1
Order By: Relevance
“…We could thus extend the results of a previous work, in which it was revealed that FGF-2 increases the expression and secretion of heparin affin regulatory peptide/ pleiotrophin, cellular proliferation and migration (Hatziapostolou et al 2006). One could hypothesise that expression of FGF-2 targets such as cyclin E, retinoblastoma or matrix metalloproteinases is affected through the effect of SOCS-3 on p44/p42 MAPK phosphorylation (Muddasani et al 2007, Takeuchi et al 2007. We demonstrate for the first time that SOCS-3 may interfere with oncogenic events caused by the p44/p42 MAPK pathway in cancer.…”
Section: Socs-3 Inhibition Of P44/p42 Mapk Antagonises Fgf-2-induced supporting
confidence: 64%
“…We could thus extend the results of a previous work, in which it was revealed that FGF-2 increases the expression and secretion of heparin affin regulatory peptide/ pleiotrophin, cellular proliferation and migration (Hatziapostolou et al 2006). One could hypothesise that expression of FGF-2 targets such as cyclin E, retinoblastoma or matrix metalloproteinases is affected through the effect of SOCS-3 on p44/p42 MAPK phosphorylation (Muddasani et al 2007, Takeuchi et al 2007. We demonstrate for the first time that SOCS-3 may interfere with oncogenic events caused by the p44/p42 MAPK pathway in cancer.…”
Section: Socs-3 Inhibition Of P44/p42 Mapk Antagonises Fgf-2-induced supporting
confidence: 64%
“…In case of bFGF, the elevations of pRB (Ser780), RB, and cyclin A protein levels in NIFr cells did not differ from those of NIFn cells, but pRB(ser780) in case of IGF-I. The growth of NIFr cells was greater than NIFn cells as a result of the active G 1 /S transition of NIFr cells, by the increments of cyclin E, pCDK2 and pRB (ser807/811) protein in NIFr cells [17,18] (Fig. 1).…”
Section: Response To Growth Factors On Cell Growth and Cell Cycle Regmentioning
confidence: 99%
“…2 [18]. NIF inhibits phosphodiesterase to increase protein kinase G, and then activates p38 mitogen-activated protein kinase (p38 MAPK) and activating transcription factor-2, resulting in apoptosis and inhibition of cell growth.…”
Section: Intracellular Crosstalkmentioning
confidence: 99%
See 2 more Smart Citations